2014
DOI: 10.1159/000360239
|View full text |Cite
|
Sign up to set email alerts
|

Peer and Romantic Relationships among Adolescent and Young Adult Survivors of Childhood Hematological Cancer: A Review of Challenges and Positive Outcomes

Abstract: This review focuses on peer and romantic relationship experiences of adolescent and young adult (AYA) survivors of childhood cancer, highlighting those surviving leukemia or lymphoma. While most AYA survivors adjust well to life following a hematological cancer diagnosis and treatment, many unique experiences, both positive and challenging, have been documented with respect to successfully navigating developmentally normative social goals. Therefore, the social implications of surviving childhood leukemia or l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Cross sectional questionnaire examining characteristics of CCS who attended vs. did not attend a LTFU clinic for CCS.N = 102 survivors who had received care at a LTFU clinic and N = 71 survivors never seen in a LTFU clinic Most common reasons that non‐LTFU survivors did not attend the clinic were “not aware” (71 %) or “not interested” (16 %). Survivors in each group were able to accurately report their cancer diagnosis, but few knew specific treatment information. Both groups underestimated their health risks. A significant minority in each group reported psychological or emotional problems (16–18 %), post‐traumatic stress disorder (4.2–6.9 %), and/or psychological distress (7.8–19.7 %) but there were no differences by receipt of LTFU care. Risky health behaviors (alcohol use, sunscreen & physical activity) between those who have attended a LTFU clinic and those who did not were not statistically different. moderate sample size; data collection appropriate to study method; appropriate analysis; reporting comprehensive, clearly described;4xxxFord, 2014 Psychosexual Functioning Among Adult Female Survivors of Childhood Cancer: A Report From the CCSS Cross sectional Survey‐basedN = 2178 female adult CCS, N = 408 female siblings Survivors reported significantly lower sexual, lower sexual interest, lower sexual desire, lower sexual arousal, lower sexual satisfaction, and lower sexual activity, compared with siblings. Risk factors for poorer psychosexual functioning among survivors included older age at assessment, ovarian failure at a younger age, treatment with cranial radiation, and cancer diagnosis during adolescence. Large sample size with sibling controls; data collection appropriate to study method; measurement bias; appropriate analysis; evidence derived from high quality cohort studies; reporting comprehensive, clearly described**4xFoster, 2014 Peer and romantic relationships among adolescent and young adult survivors of childhood hematological cancer: a review of challenges and positive outcomes Narrative ReviewStudies of Adolescent and Young Adult (AYA) CCS Both intensity and long treatment may result in atypical socialization AYA survivors also report benefits of their cancer experiences such as increased maturity, an ability to cope with life stressors, and perceptions that they can and will have the ability to be good romantic partners and parents Factors associated with the development of peer and romantic relationships among AYA survivors of childhood hematological cancers include: ◦perceived health vulnerabilities ◦body image following treatment ◦how attachment to parents relates to later social outcomes the impact of fertility concerns on later relationships and identity development Did not describe methodology for studies included, did not include a table of studies, did not appropriately assess for quality of studies.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…Cross sectional questionnaire examining characteristics of CCS who attended vs. did not attend a LTFU clinic for CCS.N = 102 survivors who had received care at a LTFU clinic and N = 71 survivors never seen in a LTFU clinic Most common reasons that non‐LTFU survivors did not attend the clinic were “not aware” (71 %) or “not interested” (16 %). Survivors in each group were able to accurately report their cancer diagnosis, but few knew specific treatment information. Both groups underestimated their health risks. A significant minority in each group reported psychological or emotional problems (16–18 %), post‐traumatic stress disorder (4.2–6.9 %), and/or psychological distress (7.8–19.7 %) but there were no differences by receipt of LTFU care. Risky health behaviors (alcohol use, sunscreen & physical activity) between those who have attended a LTFU clinic and those who did not were not statistically different. moderate sample size; data collection appropriate to study method; appropriate analysis; reporting comprehensive, clearly described;4xxxFord, 2014 Psychosexual Functioning Among Adult Female Survivors of Childhood Cancer: A Report From the CCSS Cross sectional Survey‐basedN = 2178 female adult CCS, N = 408 female siblings Survivors reported significantly lower sexual, lower sexual interest, lower sexual desire, lower sexual arousal, lower sexual satisfaction, and lower sexual activity, compared with siblings. Risk factors for poorer psychosexual functioning among survivors included older age at assessment, ovarian failure at a younger age, treatment with cranial radiation, and cancer diagnosis during adolescence. Large sample size with sibling controls; data collection appropriate to study method; measurement bias; appropriate analysis; evidence derived from high quality cohort studies; reporting comprehensive, clearly described**4xFoster, 2014 Peer and romantic relationships among adolescent and young adult survivors of childhood hematological cancer: a review of challenges and positive outcomes Narrative ReviewStudies of Adolescent and Young Adult (AYA) CCS Both intensity and long treatment may result in atypical socialization AYA survivors also report benefits of their cancer experiences such as increased maturity, an ability to cope with life stressors, and perceptions that they can and will have the ability to be good romantic partners and parents Factors associated with the development of peer and romantic relationships among AYA survivors of childhood hematological cancers include: ◦perceived health vulnerabilities ◦body image following treatment ◦how attachment to parents relates to later social outcomes the impact of fertility concerns on later relationships and identity development Did not describe methodology for studies included, did not include a table of studies, did not appropriately assess for quality of studies.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…For example, elderly people (>65 years at diagnosis) generally have to deal with a decline in physical functioning, less social support, isolation and comorbid conditions [ 13 15 ]. In contrast, adults (36–64 years at diagnosis) more often have concerns about unemployment, financial issues and family matters [ 16 , 17 ], while adolescents and young adults (AYAs; 18–35 years at cancer diagnosis) are in a challenging period where they face major life tasks, such as establishing their personal identity, creating intimate relationships, gaining independence and starting careers and families [ 18 20 ]. A cancer diagnosis at AYA age can significantly disrupt or delay achieving these milestones [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Childhood cancer survivors endorse lower sexual satisfaction and activity than their siblings and additionally note increased stress related to romantic relationships [77,78]. Research into LGBT survivorship is limited but has demonstrated increased difficulty with intimate relationships among LGBT patients [79].…”
Section: Sexualitymentioning
confidence: 99%